Diet variations and morphological changes of the rockcod Patagonotothen tessellata (Teleostei: Nototheniidae) in Chilean Central Patagonia - Hune, Mathias; Quintullanca, Alex; Aldea Venegas, Cristian Leonardo; Landaeta, Mauricio F. (My University, 2023)
This study provides the first description of the morphology (geometric morphometric analysis), condition (Fulton index), and diet (stomach content analyses) of the rockcod Patagonotothen tessellata from the coast of Chilean Central Patagonia. We found low but significant intersexual variability in the snout extension, mouth size, and the insertion of the pelvic fin supporting the presence of sexual shape dimorphism in P. tessellata. The diet of the males showed a preference for Patagonotothen spp., unidentified crustaceans, and polychaetes (Chaetopteridae), while the diet of females was comprised primarily of unidentified fish and crustaceans. Significant differences in the consumption of algae, other invertebrates, and fishes were observed between sexes, and a significant negative correlation between fish length and the ingestion of amphipods was found. Diet composition showed significant differences between sexes, but not among size groups. Finally, a partial least square analysis showed a weak but significant covariance between diet and morphology: individuals with shorter snouts and smaller eyes had more unidentified crustaceans, amphipods, and fish in their stomach contents, while individuals with narrower trunks contained more unidentified crustaceans, the shrimp Betaeus truncatus, and gastropods; and individuals with slenderer heads had more Patagonotothen spp. in their stomachs.
Keywords: feeding ecology; geometric morphometrics; ecomorphology; sexual dimorphism; notothenioidei